Undiagnosed Gestational Diabetes Mellitus and Its Impact on Maternal and Perinatal Outcomes: A Systematic Review - Sabrina, Ardini; Yeni, Cut Meurah; Pravasta, Iqbal Aryo (Yayasan Sagita Akademia Maju, 2026)
Gestational diabetes mellitus (GDM) was a common metabolic disorder during pregnancy associated with significant maternal and neonatal morbidity. Although outcomes of diagnosed and treated GDM had been well established, some cases remained unrecognized because of variations in screening implementation and diagnostic thresholds. This study aimed to evaluate the association between undiagnosed GDM and adverse maternal and perinatal outcomes. A systematic review was conducted in accordance with PRISMA guidelines. PubMed, ScienceDirect, and Google Scholar were searched for eligible observational studies. Undiagnosed GDM was categorized into four subtypes: diagnostic misclassification, mild untreated hyperglycemia with one abnormal oral glucose tolerance test value, late-diagnosed GDM, and postpartum reclassified diabetes. Methodological quality was assessed using the Newcastle–Ottawa Scale. Where comparable adjusted effect estimates were available, a random-effects meta-analysis was performed; otherwise, findings were synthesized narratively. Fourteen observational studies were included. Undiagnosed GDM was consistently associated with increased risks of hypertensive disorders, cesarean delivery, large-for-gestational-age infants, neonatal morbidity, and perinatal mortality in some cohorts. A meta-analysis of four studies showed a significantly increased risk of large-for-gestational-age infants among undiagnosed cases (pooled odds ratio = 1.77; 95% confidence interval: 1.41–2.23), with substantial heterogeneity. In several analyses, outcomes among undiagnosed cases were comparable to or more severe than those in diagnosed and treated GDM. Undiagnosed gestational dysglycemia was associated with elevated maternal and perinatal morbidity. Improving antenatal screening, diagnostic harmonization, and timely identification of hyperglycemia during pregnancy were important to reduce preventable complications.